The microstructure evolution and tensile properties of medium-Mn steel heat-treated by a two-step annealing process. (10th June 2021) - Yang, D.P.; Du, P.J.; Wu, D.; Yi, H.L.
Abstract: The martensitic hot-rolled 0.3C-6Mn-1.5Si (wt%) steel was annealed at 630 °C for 24 h to improve its cold rollability, followed by cold rolling and annealing at 670 °C for 10 min. The annealing process was designed based on the capacities of industrial batch annealing and continuous annealing lines. A duplex submicron austenite and ferrite microstructure and excellent tensile properties were obtained finally, proved the above process is feasible. "Austenite memory" was found in the hot-rolled and annealed sample which restricted recrystallization of lath martensite, leading to lath-shaped morphology of austenite and ferrite grains. "Austenite memory" disappeared in the cold-rolled and annealed sample due to austenite random nucleation and ferrite recrystallization, resulting in globular microstructure and refinement of both austenite and ferrite grains. The austenite to martensite transformation contributed most of strain hardening during deformation and improved the uniform elongation, but the dislocation strengthening played a decisive role on the yielding behavior. The tensile curves change from continuous to discontinuous yielding as the increase of cold-rolled reduction due to the weakening dislocation strengthening of austenite and ferrite grains related to the morphology change and grain refinement. A method by controlling the cold-rolled reduction is proposed to avoid the Lüders strain.